Tax Control in the System of Taxes Administration - Olha Zhuk (Vasyl Stefanyk Precarpathian National University, 2019)
The article deals with the features of tax control in the system of tax administration. The main stages and peculiarities of implementation of tax control are highlighted on each of them. The principles and functions of tax control which will ensure the efficiency and effectiveness of this process are determined. The main forms and peculiarities of tax control are described.